Does modifying competition affect the frequency of technical skills in junior rugby league? - Morley, D.; Ogilvie, P.; Till, K.; Rothwell, M.; Cotton, W.; O`Connor, D.; McKenna, J. (International Journal of Sports Science & Coaching, 2016)
The technical demands of games can be affected by changing the number of players, pitch size and rules. This controlled trial compared the frequency of technical skills between a `traditional` and newly introduced systematically `modified` game of primary rugby league. A total of 475 primary rugby league players (Under 7s to 9s) were filmed playing traditional (n=49) and modified (n=249) formats. Notational analysis examined the frequency of technical skills (e.g. number of passes) within `traditional` and `modified` games. At each age category, multivariate analysis of variance indicated the clear superiority of the `modified` game for the frequency of technical skills (e.g. Under 7s total skill opportunities - `traditional`=342.9±47.0; `modified`=449.4±93.3, d=1.44, p<0.001). Systematically modifying the competitive game is an effective way to increase skill opportunities for children within rugby league. Future research should examine the outcomes of modifying games in optimizing skill development in youth sport. ABSTRACT FROM AUTHOR